Detection of proteins antigenically related to Bothrops asper myotoxin in crotaline snake venoms - Lomonte, Bruno (1987)
The presence of components antigenically related to Bothrops asper myotoxin was investigated by Western blotting and immunoelectrophoretic techniques. B. asper myotoxin is a non-glycosylated monomeric phospholipase A with a molecular weight by SDS-PAGE of 16,000 and isoelectric point of pH 9.8-10.0. Results showed that proteins in the venoms of B. nummifer, B. godmani, B. schlegelii, B. picadoi, and Agkistrodon bilineatus were recognized by monospecific antibodies to B. asper myotoxin raised in rabbit and sheep. Western blotting indicated that cross-reacting proteins have a molecular weight of 16,000, with the exception of that of B. picadoi, which is of 24,000 mol. wt. However, immunoelectrophoresis indicated that these components are highly heterogeneous in charge, ranging from basic to acidic proteins. The cross-reacting component(s) present in newborn B. asper venom has a different charge from that of the 'adult-type'. Venoms from newborn specimens showed an additional cross-reacting band of 18,000 mol. wt. Myotoxin is an abundant component in adult B. asper venom. Myotoxin-antimyotoxin complexes had different electrophoretic mobilities in rocket immunoelectrophoresis depending upon the species in which monospecific immune sera were produced.